The ethics as character and medical research - Drane, James F. (Acta Bioethica, 2004)
With this paper I intend to draw attention again to the historic connection between the original meaning of the Greek word ethos and the discipline of ethics, as inner self, human spirit or character. The ethics of research must include the inner dimension of ethics just as norms and guidelines for behavior are included. We learn from the history of the ethics of research that transgressions have occurred not due to lack of norms and guidelines, but because of ignoring the inner dimension of ethics. Today, medical researchers are subjected to self promotion temptations driven by narcissism and avarice, which can lead them to ignore this inner dimension. Today´s researchers will not yield to the pressures of following their own interests if they learn from the example of the origin of the Middle Ages' Hospitable Knights and from researchers such as Henry K. Beecher.